Recurrent Alcoholic Cirrhosis In Severe Alcoholic Relapse After Liver Transplantation: A Frequent and Serious Complication. (August 2015) - Dumortier, Jérôme; Dharancy, Sébastien; Cannesson, Amélie; Lassailly, Guillaume; Rolland, Benjamin; Pruvot, François‐René; Boillot, Olivier; Faure, Stéphanie; Guillaud, Olivier; Rigole‐Donnadieu, Hélène; Herrero, Astrid; Scoazec, Jean‐Yves; et al.
Abstract : Objectives: Alcoholic liver disease (ALD) is a major indication for liver transplantation (LT). Recurrent alcoholic cirrhosis (RAC) after LT can occur but has not been studied. The aims of this study were to estimate the prevalence, predictive factors, and natural history of RAC after LT. Methods: All patients transplanted for ALD between 1990 and 2007 in three French centers were included. The diagnosis of RAC was based on histological evidence or a series of features combined with severe alcoholic relapse. Results: Among 1, 894 adult LT patients, 712 were transplanted for alcoholic cirrhosis and survived >6 months. After a mean follow‐up of 9 years, 128 patients (mean age at LT 47.2±7.1 years old, 78.9% men) experienced severe alcoholic relapse (18.0% of cases). Severe alcoholic relapse occurred after a median delay of 25 months (range 4–157) after LT. RAC was diagnosed in 41 patients with severe relapse (32%). The diagnosis of RAC was made after a median delay of 5.1 years (range 1.8–13.9) after LT and of 4.0 years (range 1.2–11.5) after relapse. RAC was significantly associated with younger age and a shorter period of pre‐LT abstinence. One‐, 5‐, 10‐, and 15‐year survival was 100, 87.6, 49.7, and 21.0%, respectively, for RAC patients vs. 100, 89.4, 69.9, and 41.1%, respectively, for the patients without RAC ( P <0.001). Conclusions: RAC occurs in <6% of ALD transplant patients. One‐third of severe alcoholic relapse patients develop RAC <5 years after transplantation with a very poor prognosis.